(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Securing the network communication for the smart grid, it is important that a secure key distribution and management scheme is needed. Advanced metering Infrastructure (AMI) is considered as integral part of the smart grid that collects and analyzes the information of energy consumption using the communication network. In order to achieve data confidentiality, privacy, and authentication in AMI, various crypto algorithms are used, such as demand key distribution and management schemes. Investigation on properly designed key distribution and management scheme for securely gathering both individual and aggregated meter’s readings is one of the critical requirements. In this paper, we propose a secure key distribution for Home Area Network (HAN) in smart grid. In this paper, we propose a new key distribution and management scheme, which uses identification scheme of Wu – Hsu and tailored to smart grid. We also give the scheme for key update/freshness and key revocation. Specifically, a group ID based mechanism is proposed to establish the keys for a large amount of users with small overload.